Characterization of intracellular pathways leading to coinduction of thrombospondin-1 and TGF-β1 expression in rat hepatic stellate cells - Breitkopf-Heinlein, Katja; Sawitza, Iris; Gressner, Axel M. (Growth factors, 2005)
Accumulating evidence has identified Thrombospondin (TSP)-1 as important activator of latent TGF-β. Since little is known about signal transduction pathways regulating TSP expression in liver, we investigated cytokine-mediated upregulation of TSP-1 and TGF-β1 in primary rat hepatic stellate cells (HSC). PDGF-BB and TNF-α rapidly coinduce mRNA levels of TSP-1 and TGF-β1. Interestingly, blockade of basal Erk activity by synthetic Erk-binding peptides also leads to strong induction of both mRNA transcripts in non-stimulated cells. We show that PDGF-BB induces TSP-1 and TGF-β1 via the src kinase pathway whereas TNF-α utilizes the MAPK/Erk pathway. However, especially TSP-1 induction by both cytokines involves a pathway, which depends to a certain extent on PI3 kinase activity.In summary the data illustrate specific pathways activated by PDGF-BB and TNF-α in HSC giving new insights into the tightly controlled mechanisms regulating TSP-1 and TGF-β1 expression in these cells.
Elektronische Reproduktion der Druck-Ausgabe
Published online: 11 Jul 2009
Gesehen am 23.06.2022